2020
DOI: 10.5296/jas.v8i3.16243
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Nutrition of Oil Palm Tree (Elaeis Guinq Jacq) in Eastern Amazon

Abstract: In Brazil, the status of chlorine (Cl) nutrition in plants is still poorly studied. The micronutrient Cl plays an important role in cultures such as coconut and oil palm trees. This study aimed to evaluate the status of chlorine nutrition in oil palm trees as a function of planting age, which ranged from two to eight years of cultivation. The experiment was conducted in Tailândia, state of Pará, Brazil. The soil of the area is characterized as Yellow Latosol of medium texture. A total of four oil palm trees we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…On the other hand, male inflorescences showed less variation (26%) in Mn concentrations (82.0 to 103.75 mg kg -1 of Mn). Viégas et al (2020), evaluating Cl in oil palm trees, also observed greater variation in the nutrient contents in the palm heart of the plants. According to these authors, these variations alter the metabolism of the plant and, consequently, the uptake rates of nutrients, since at the beginning of vegetative development the production is still relatively low (6 to 8 t ha -1 year -1 bunches), gradually increasing until the plants reach eight years, reaching the maximum yield of 20 to 30 t ha -1 year -1 of bunches.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, male inflorescences showed less variation (26%) in Mn concentrations (82.0 to 103.75 mg kg -1 of Mn). Viégas et al (2020), evaluating Cl in oil palm trees, also observed greater variation in the nutrient contents in the palm heart of the plants. According to these authors, these variations alter the metabolism of the plant and, consequently, the uptake rates of nutrients, since at the beginning of vegetative development the production is still relatively low (6 to 8 t ha -1 year -1 bunches), gradually increasing until the plants reach eight years, reaching the maximum yield of 20 to 30 t ha -1 year -1 of bunches.…”
Section: Resultsmentioning
confidence: 88%
“…The nutritional needs of oil palm are large and vary widely, depending on yield, planted genotype, spacing, palm age, type and soil cover conditions, climate, and other environmental factors (Woittiez et al, 2017). About the micronutrients, there are few long-term studies developed with oil palm plants, however, some reports are found in the literature (Viégas et al, 2019;Viégas et al, 2020;Viégas et al, 2021). The evaluation of commercial oil palm nutrition in Pará pointed to Zn and Mn as the most deficient micronutrients in this palm tree (Matos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Variation of P concentrations was higher in palm heart (Table 3). Viegas et al (2020) evaluated Cl in oil palm and observed greater variation in P concentrations in palm heart of plants. According to the authors, these variations alter plant metabolism and, consequently, the absorption rates of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, some researchers seek to remedy the existing gaps in the field of soil fertility in the Amazon region, researching the nutritional needs of the main crops for the region (Lima et al, 2018;Silva et al, 2018;Mera et al, 2020;Viégas et al, 2020;Tanaka et al, 2020;Lima et al, 2020). Research, Society and Development, v. 10, n. 1, e36110111721, 2021 (CC BY 4.…”
Section: Introductionmentioning
confidence: 99%